PENGGUNAAN METODE BERCERITA DALAM MENGEMBANGKAN BAHASA EKSPRESIF ANAK USIA 5 -6 TAHUN DI PAUD KASIH IBU KOTA SERANG - Eka Safitri; Nuryati; Beni Junedi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
In the development of early childhood expressive language at PAUD Kober Kasih Ibu, several problems were found to be the lack of appropriate and interesting learning methods. One of the methods that is believed to be effective but has not been optimally applied is the storytelling method. Initial observations show that there are problems in the development of early childhood expressive language in PAUD Kober Kasih Ibu, especially related to the limitations of appropriate and interesting learning methods. Although the storytelling method is believed to have effective potential, its application in the field is considered not optimal. Departing from this background, this study focuses mainly on describing how storytelling methods can improve the ability of children aged 5–6 years to express their thoughts, ideas, and feelings verbally. The main purpose of this study is to determine the effectiveness and impact of the application of storytelling methods on children's expressive language skills, as well as to describe in depth how to develop these skills in PAUD Kasih Ibu. This study uses a descriptive qualitative approach. Data collection was carried out through triangulation techniques, namely observation of 5 children, in-depth interviews with 3 teachers, and documentation, in order to obtain a comprehensive and contextual picture of the phenomenon being studied. The results of the research and discussion indicate that the storytelling method is able to create an active, fun learning atmosphere, and encourage children's verbal participation. Children seem more enthusiastic, focused on listening, and dare to speak and respond to the stories told by the teacher. The use of this method has proven to be effective in supporting a more interactive and communicative learning process, as well as providing a meaningful learning experience for children.